Approximation and online algorithms : 13th International Workshop, WAOA 2015, Patras, Greece, September 17-18, 2015, revised selected papers /: 13th International Workshop, WAOA 2015, Patras, Greece, September 17-18, 2015, revised selected papers. (2015) - Unknown
No abstract available